Design of community hydropower storage for agriculture in Thailand’s highland area - Kerdphol, Thongchart; Khakkharho, Dhamrongsak; Anantarativakorn, Pongsakorn; Sukmanont, Nottakorn (Thailand Electrical Engineering Journal (TEEJ), 2025)
Thailand’s diverse geography is a factor that has made agriculture a major occupation in Thailand for long time ago. In the northern area of the country, the land is a plateau, so it is still hard to get water for farming. Therefore, farmers cannot farm in a sustainable way. This problem led to a study aimed at finding a solution and designing a Pumped-Storage Hydropower (PSH) system combined with Solar Photovoltaic (PV) system. Its goal is to help farmers gain access to water for highland agriculture. The Sop Mae Phae community in Mae Suat subdistrict, Sop Moei district, Mae Hong Son province, is a prototype study area. This study is conducted in collaboration with the Royal Irrigation Department, Region 2. The integration of the two systems in this study shows potential to reduce water acquisition costs, enhance the long-term stability of agricultural water use and sustain agricultural activities over time. This approach addresses drought, stabilizes the economy, and removes highland agriculture limits. This study employed reliable software tools for the pumped-storage hydropower was designed using Pipe Flow Expert 7.4®, while the Solar Photovoltaic system was designed using PVsyst 8®. By addressing the key issues related to water access and geographical constraints, this study provides a pathway for farmers in northern Thailand to maintain agricultural productivity sustainably.